Bevacizumab and other novel therapies for recurrent oligodendroglial tumors. (October 2015) - Grimm, Sean A; Chamberlain, Marc C
Oligodendroglioma (WHO Grade 2) and anaplastic oligodendroglioma (WHO Grade 3) are glial tumors composed of neoplastic cellular elements that resemble oligodendrocytes. The treatment of recurrent, alkylator refractory oligodendroglial tumors is challenging given the paucity of effective treatment and lack of randomized controlled trials on which to base therapy. Notwithstanding the lack of prospective, randomized data, treatment of oligodendroglial tumors with bevacizumab can be recommended tentatively recognizing that preliminary studies suggest efficacy. Somatic mutations of the isocitrate dehydrogenase enzymes (IDH1 and IDH2) appear to play a critical role in the pathogenesis of most oligodendroglial tumors and agents that target these mutations are a potential therapeutic option. Additionally, reversal of CpG island hypermethylated phenotype status through inhibition of DNA methyltransferase with an inhibitor such as decitabine may provide a target for future studies.